Early use of steroid‐sparing agents in the inactivation of moderate‐to‐severe active thyroid eye disease: a step‐down approach. (11th September 2018) - Sipkova, Zuzana; Insull, Elizabeth A.; David, Joel; Turner, Helen E.; Keren, Shay; Norris, Jonathan H.
Summary: Objectives: The current first‐line treatment for management of active thyroid eye disease (TED) is high‐dose intravenous corticosteroids, which have the potential for serious adverse effects. Our aim was to evaluate the effect of steroid‐sparing agents (SSAs) in patients with moderate‐to‐severe active TED, using methotrexate as first‐line. Methods: Presented is a retrospective, four‐year, single‐centre, consecutive case series of patients with moderate‐to‐severe TED treated using the Oxford protocol. Treatment modality, disease activity, and adverse effects are reported at presentation, 6‐ and 12‐month follow‐up. Results: 104 consecutive TED patients treated by the Oxford TED team were reviewed. 24 patients with moderate‐to‐severe active disease were identified (mean age 46.8 years;12 female) with a mean pretreatment VISA inflammatory index score of 5.5/10 (SD = 1.98; range 1‐9). Intravenous methyl‐prednisolone (IVMP) and an SSA was commenced in all patients. Mean total steroid dose was 2.72 g (SD = 1.4;1.0‐6.9). 38% of patients (n = 9) received ≤1.5 g of IVMP. Only two patients required >4.5 g of IVMP equating to the EUGOGO treatment protocol dose for this patient group. There was significant improvement in inflammatory index score both at the intermediate review (mean score 2.7; SD = 2.8; P  <   0.001; mean follow up 25.2 weeks) and at one year or last follow‐up (mean score 1.4; SD = 1.5; P  <   0.001; mean follow up 48.0 weeks). No serious or long‐term adverse effects were reported. Conclusion: This study suggests that the initiation of an SSA, using methotrexate as first‐line, with limited adjuvant IVMP is an effective and safe treatment for moderate‐to‐severely active TED, resulting in a significant reduction in both disease activity and total steroid load.